PELAKSANAAN BIMBINGAN BELAJAR TERPIMPIN BERBASIS TEAMWORK DALAM MENINGKATKAN KEMAMPUAN BELAJAR SISWA SMA NEGERI 1 SUNGGAL - Elza Leyli Lisnora Saragih; Erly Farida Siadari; Sentinawati Siagian; Meliana Simanjuntak; Rusli Situmorang (CV SWA Anugerah, 2025)
This study aims to explore the effectiveness of guided learning based on teamwork in improving the learning abilities of students at SMA Negeri 1 Sunggal. This research uses a qualitative research method with data collection techniques through observation, interviews, and analysis of academic test results. The results show that guided learning based on teamwork can improve students' learning abilities, particularly in terms of understanding concepts and materials, as well as applying knowledge in different situations. This guidance program also increases students' learning motivation and facilitates collaboration and interaction among students.